Severe Atelectasis due to Aspirated Valproic Acid Tablet - Tomomi Tanigaki; Takunori Ogawa; Sakika Nomura; Koki Ito; Yuhei Kurata; Akira Matsukida; Morio Ishihara; Aihide Yoshino; Akihiko Kawana; Yoshifumi Kimizuka (Case Reports in Pulmonology)
A 60-year-old man treated with valproic acid (VPA) for epilepsy developed atelectasis and respiratory failure after an accidentally aspirated VPA tablet-induced mucus hypersecretion. Following bronchoscopic removal of the aspirated tablet, his respiratory status improved and massive sputum production did not recur. We hypothesized that the aspirated VPA tablet increased the expression of mucin-related genes, thereby increasing mucus production. Our in vitro experiments using a human respiratory epithelial cell line revealed that VPA directly upregulates the airway mucin-related genes. We believe that this is the first case report of aspirated VPA-induced severe atelectasis and respiratory failure, which were successfully treated with the bronchoscopic removal of the VPA tablet.